Terminally redundant deletion mutants of bacteriophage BF23. - Shaw, A R (1979)
Deletion mutants of bacteriophage BF23 were isolated and the positions of the deletions were determined. Two different deletable regions were detected: one in the same region as previously reported for bacteriophage T5, which is closely related to BF23; and the other within both terminal repetitions. The former deletable region lay between positions 0.31 and 0.36, which represented the fractional lengths of the BF23 ( + ) DNA as measured from its left end. The latter deletion was evenly divided between the two terminal repetitions. The deletion in the left terminal repetition lay between positions 0.044 and 0.078 and was repeated in the corresponding region of the right terminal repetition between positions 0.966 and 1.0. The size of the DNA transferred to host cells during the first step of DNA transfer by BF23 carrying deletions in the terminal repetitions of its DNA was less than the size of DNA transferred during the first step by wild-type BF23 by an amount equal to the size of the deletion in each terminal repetition. This finding suggests the existence of a specific mechanism for delineating the position at which the first step of DNA transfer is stopped.